Security and data reliability in cooperative wireless networks - Hassan, Emad S. (CRC Press, Taylor & Francis Group, 2018)
Following a detailed overview of cooperative communications and the physical layer security, this book proposes relay and jammer selection schemes for security in one-way cooperative networks and to improve physical layer security in two-way cooperative networks. It also proposes a Cooperative Hybrid Self-Healing scheme to enhance the confidentiality of the data collected by UWSN. It ends with a proposal called Self-Healing Cluster Controlled Mobility (SH-CCM) scheme based on hybrid cooperation between both Proactive and Reactive peers and the sick sensors at both network and cluster levels to guarantee the security in UWSN- Resumé vydavatel
Keywords: bezdrátové senzorové sítě; spolehlivost (technika); počítačové systémy; wireless sensor networks; reliability (engineering); computer systems; monografie; elektronické knihy; monographs; electronic books